THE ANALYSIS OF PUBLIC TENDENCY ON ONLINE MEDIA TRIBUN NEWS ACORDING TO READERS - Fadhilah Nur Rohmah; Zahra Raisya Bawier; Wahyunengsih Wahyunengsih (Lafadz Jaya Publisher, 2022)
From the past until now, the mass media has always been in the spotlight of the public. The public spotlight on the assessment of the mass media in conveying a news or event is sometimes not always objective and not neutral. Some of the mass media that convey a news story is still mostly in favor of a particular group or interest. Even though the idealism of the news displayed by a media is the embodiment of the existing reality. The purpose of this study is to analyze where the alignment of one of the mass media, namely tribunnews, is, whether the information conveyed is objective and neutral in conveying information. This study uses a questionnaire method in the form of a google form that we distribute to students who have read news from the online media tribunnews. The results of the questionnaires that we distributed for 3 days, respondents said that the online media tribunnews was quite neutral and objective in conveying news or information. Then the results of the questionnaire stated that the online mass media Tribunne News was impartial or could be called neutral and accurate. Because the media spreads news that is factual or in accordance with the facts of what happened at that time.